Kedaulatan di Ruang Siber: Strategi Pengembangan Kapabilitas Perwira Hukum TNI AL - Tri Arianto; Muhammad Zulkifli (EduInovasi: Journal of Basic Educational Studies, 2026)
The dynamics of contemporary maritime security threats have evolved significantly, with cyberspace now established as a critical domain that complements the traditional tri-matra (three-dimensional warfare). Threats such as sabotage of Command and Control (C2) systems, digitally-based maritime spionage, and disinformation campaigns that disrupt naval operations require a nimble legal response underpinned by profound technical knowledge. This conceptual article argues that fulfilling the requirements for Indonesian Navy (TNI AL) Legal Corps Officers is no longer sufficient through conventional legal education alone; instead, it demands a fundamental reorientation of the Initial Officer Education (Dikma) and Specialist Development Education (Dikbangspes) programs. Through a thorough needs assessment approach, this article proposes an integrative framework that unites three main pillars: international cyber law principles (jus in silico), applicable digital forensic technical competencies, and specific maritime operational contexts. Case simulations, such as handling data breach incidents aboard warships or conducting legal analysis of cyber attacks on port infrastructure, are proposed as methods for evaluating program effectiveness. In conclusion, this curriculum transformation serves as a crucial force multiplier for building robust and proactive legal advisory capabilities, thereby ensuring Indonesia's legal sovereignty in the future digital maritime domain.